An exposition and evaluation of John Calvin's teaching on the sacraments, with particular reference to the sacrament of the Lord's supper in its liturgical context - Orr, Robert (Rhodes University, Faculty of Divinity, Department of Divinity, 1954)
Misinterpretations of John Calvin's theology are legion. It is hoped that this thesis does not add to their number. The basis for this lies in the fact that the task of writing on the subject has of course compelled the writer to do his utmost to comprehend what Calvin had to say concerning the Sacraments both in the Institutions and in the Scriptural Commentaries ... .The attempt has been made to refract Calvin's thought on the Sacrament, using certain key-concepts as prisms, and from the results thus obtained, to draw certain conclusions from which, it is hoped, will not be unprofitable to the life of the Holy Catholic Church. It is thus to be reagrded as an essay in historical theology rather than a whole-hearted attempt to reconstruct Calvin's exposition of the sacrament in the light of what has been revealed to us in the intervening years.
Keywords: Lord's Supper (Liturgy) -- History; Sacraments -- Reformed Church; Calvin, Jean, 1509-1564